2022
DOI: 10.1007/s00296-022-05091-7
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma release assays outcomes in healthy subjects following BNT162b2 mRNA COVID-19 vaccination

Abstract: The pathogenesis of COVID-19 involves both humoral and cellular immunological responses, with cell-mediated immunity being discussed as the primary and most effective immune response to viral infection. It is supposed that COVID-19 vaccines also elicited effective cell immune response, and specifically IFNγ secreted by SARS-CoV-2-specific T-helper 1 and Tcytotoxic cells. Using an interferon-gamma release assay (IGRA) test, we aimed to monitor cellular post-vaccination immunity in healthy subjects vaccinated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 18 publications
1
30
1
3
Order By: Relevance
“…At our knowledge, this is the first study that evaluated T-cell immunity response and explored its potential predictors in a large, representative sample of real-world hospital workers, at a median time elapsed greater than 7 months after second-dose vaccine administration. Few studies have evaluated T-cell responses after two doses of the BNT162b2 vaccine and mainly focused on recently vaccinated individuals (i.e., first two months post-vaccination) or on smaller series [ 19 ]; higher rates of T-cell responsiveness compared to those observed in our study were often observed [ 20 , 21 , 22 ], similar to the rates reported for humoral responses [ 9 ], a finding consistent with a decline in T-cell mediated responses over time observed by others [ 10 , 12 , 23 ] as well as in the present study. However, it is noteworthy that in our study a cellular response ≥ 0.15 IU/mL persists up to 7 months post-vaccination in more than 60–70% of subjects (depending on the Ag), also among subjects without previous SARS-CoV-2 infection ( Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…At our knowledge, this is the first study that evaluated T-cell immunity response and explored its potential predictors in a large, representative sample of real-world hospital workers, at a median time elapsed greater than 7 months after second-dose vaccine administration. Few studies have evaluated T-cell responses after two doses of the BNT162b2 vaccine and mainly focused on recently vaccinated individuals (i.e., first two months post-vaccination) or on smaller series [ 19 ]; higher rates of T-cell responsiveness compared to those observed in our study were often observed [ 20 , 21 , 22 ], similar to the rates reported for humoral responses [ 9 ], a finding consistent with a decline in T-cell mediated responses over time observed by others [ 10 , 12 , 23 ] as well as in the present study. However, it is noteworthy that in our study a cellular response ≥ 0.15 IU/mL persists up to 7 months post-vaccination in more than 60–70% of subjects (depending on the Ag), also among subjects without previous SARS-CoV-2 infection ( Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bulgaria and the Bulgarian public health system were also in a difficult situation. In this regard, several studies on SARS-CoV-2 infection had been conducted in our country, including: a seroepidemiological survey [ 10 ]; research on clinical characteristics of patients with COVID-19 [ 11 , 12 ]; studies of immune response to SARS-CoV-2 vaccines [ 13 , 14 , 15 ]; research into adverse events of COVID-19 vaccines [ 16 ]; studies dealing with inconclusive SARS-CoV-2 PCR samples [ 17 ]; and studies of liver involvement in children with COVID-19 and multisystem inflammatory syndrome [ 18 ]. The Bulgarian vaccination process started on 26 December 2020.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of two doses of mRNA vaccines for COVID‐19 prevention for a variable length of time has been reported by many authors. 14 , 15 , 16 , 17 , 18 Interesting are the studies on the so‐called “extended vaccine schedules.” 19 , 20 , 21 According to the authors, increasing the interval between the first and second doses from 3 weeks to 11–12 weeks for the Comirnaty vaccine, increased the peak of antibody production.…”
Section: Discussionmentioning
confidence: 99%